Effect Destination Image of Revisit Intention Through Memorable Tourist Experience and Tourist Satisfaction in Destination Karimunjawa, Indonesia - Anggraini, Filda; Komaryatin, Nurul (Manunggal Halim Jaya, 2025)
This study aims to analyze the influence of Destination Image on Revisit Intention, with Memorable Tourist Experience and Tourist Satisfaction as mediating variables in the Karimunjawa Island destination. A quantitative approach was employed, collecting data through online questionnaires distributed to 192 respondents. The data was analyzed using a structural model through the SmartPLS 4.0 application. The results indicate that Destination Image has a positive and significant effect on Memorable Tourist Experience (coefficient 0.840, p < 0.05) and Tourist Satisfaction (coefficient 0.828, p < 0.05). Moreover, Tourist Satisfaction fully mediates the relationship between Destination Image and Revisit Intention (coefficient 0.701, p < 0.05), while Memorable Tourist Experience does not have a significant effect on Revisit Intention (coefficient -0.231, p > 0.05). Based on these findings, the study concludes that destination managers should focus on strengthening the destination image and enhancing tourist satisfaction to increase revisit intention in Karimunjawa.